2008
DOI: 10.1007/bf03345655
|View full text |Cite
|
Sign up to set email alerts
|

Effect of very low LDL-cholesterol on cortisol synthesis

Abstract: Our data reflect that having serum LDL-cholesterol levels below 70 mg/dl did not affect the adrenal axis function in terms of cortisol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…Cholesterol forms the basic structure of many hormones (e.g. cortisol, aldosterone) (1). Of interest, this patient had a relatively low total cholesterol and LDL cholesterol.…”
Section: Discussionmentioning
confidence: 85%
“…Cholesterol forms the basic structure of many hormones (e.g. cortisol, aldosterone) (1). Of interest, this patient had a relatively low total cholesterol and LDL cholesterol.…”
Section: Discussionmentioning
confidence: 85%
“…Specifically, concern has been raised regarding the impact of lowering LDL‐C and TC on hormonal synthesis and neural development. However, several studies have not shown impact on either adrenal or testicular steroidogenesis with pharmacologic lowering of LDL‐C to levels <70 mg/dL, 15,16 and statin therapy has been associated with a reduced incidence of dementia 17 . Finally, there is concern of an increased incidence of cancer with lipid‐lowering therapy.…”
Section: Discussionmentioning
confidence: 99%
“…27,31 In another study of patients selected on the basis of LDL-C <1.8 mmol/L (70 mg/dL), with a mean LDL-C of 1.5 mmol/L (58 mg/dL), adrenal function was also normal. 50 In our study, we observed no evidence of hypoadrenalism (decreased cortisol, increased ACTH, or a decreased cortisol:ACTH ratio) in evolocumab-treated patients, even in those achieving very low LDL-C. The statistically significant increase in cortisol among evolocumab-treated patients was an unexpected finding but is likely not of clinical significance given the small absolute increase from a mean of 377.2±156.73 nmol/L at baseline to 404.1±146.89 nmol/L at week 52.…”
Section: 22mentioning
confidence: 99%